Features of Postoperative Management of Patients after Osteosynthesis of Intra- and Periarticular Fractures of the Distal Section of the Humerus: a Prospective Study - Dmitry V. Kvasov; Eduard I. Solod; Kazbek K. Bekshokov (Вестник восстановительной медицины)
INTRODUCTION. Distal humerus fractures (DHF) often cause blocking of movements in the elbow joint (EJ) and can also lead to disability. This is due to the fact that active movements in the elbow joint after such injuries are almost completely excluded. These injuries can also lead to serious consequences in adult patients, such as delayed tissue regeneration, contractures and consolidation of bone fragments in a functionally disadvantageous position. In case of forced long-term immobilization due to fractures in the lower third of the humerus, the patient and medical staff must make significant efforts to eliminate persistent contractures and restore the former mobility in the elbow joint. In addition, the risk of developing arthrosis in the future in these patients also increases if rehabilitation measures are not carried out in full. All this means that the prevention of post-traumatic contractures and arthrosis in the elbow joint after damage to its bone and/or soft tissue structures remains a topical issue for scientific research.